The Relationship between Obesity and Joint Injury History and Arthritis Incidence at Productive Age (15 – 59 Years) at West City Health Center in 2026 - Julfikra Paputungan; Sirajuddien Bialangi; Yasir Mokodompis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Arthritis is an inflammatory condition in the joints that can cause changes in bone position, accompanied by swelling, pain, stiffness, and limited movement, which are influenced by various factors including obesity and a history of joint injuries. This disease is one of the non-communicable diseases whose prevalence continues to increase and now occurs in many productive ages. In Gorontalo City, the number of arthritis cases increased from 2,769 cases in 2023 to 2,992 cases in 2024, with 87.79% of sufferers being of productive age. Therefore, this study aims to determine the relationship between obesity and history of joint injuries and the incidence of arthritis at productive age (15–59 years) at the West City Health Center in 2026. This study uses an observational analytical method with a cross-sectional design. The population in this study is patients of productive age at the West City Health Center, with a sample of 87 respondents selected using accidental sampling techniques. Data was collected through questionnaires, then analyzed using the chi-square test. Results showed a significant relationship between obesity (p=0.001) and history of joint injury (p=0.026) and the incidence of arthritis. The conclusion of this study is that obesity and a history of joint injury have a significant relationship with the incidence of arthritis at productive age at the West City Health Center in 2026. Thus, prevention efforts through weight control, increased physical activity, and proper handling of joint injuries need to be carried out to reduce the risk of arthritis occurrence at productive age.